Optimalisasi Market Share Lembaga Keuangan Syariah di Indonesia melalui Pembiayaan Sektor Rural - Zaid; Muhammad Findi; Hari Susanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
As an agricultural country, Indonesia until now has not been able to maximize the existing natural potential and the potential of the workforce, the majority of whom earn a living as farmers. This is evidenced by the narrowing of agricultural land due to the conversion of available land for other businesses and the level of welfare of farmers who are still far from being achieved, this has led to a lack of interest in today's society to become farmers.This research uses a qualitative method with a descriptive analysis approach and with data sources from the library research method. Based on the research conducted, there are several things that can be applied so that the rural sektor in Indonesia can be more advanced and able to prosper farmers, among the things that can be applied are to optimize the use of sharia insurance in agriculture in order to guarantee farmers the uncertainty of the harvest, re-establish special agricultural financial institutions that were once established or by applying contracts that have been applied in various agricultural banks in the world into financing by Islamic financial institutions, especially with Salam contracts.